Crack growth in Fe-Si (2 wt%) single crystals on macroscopic and atomistic level - Martin Ševčík; Jan Zídek; Jitka Nejezchlebová; Jan Štefan; Anna Machová; Hanuš Seiner; Alena Uhnáková; Jaroslav Čapek; Pavel Lejček (Results in Physics, 2019)
This paper is dedicated to experimental and atomistic study of the influence of so called T-stress (acting along the crack plane) on fracture processes in bcc iron. We analyze experimental results from fracture tests performed at room temperature on bcc iron-silicon single crystals with a long edge crack (1¯10)[1 1 0] (crack plane/crack front). The specimens were loaded in tension mode I under different border conditions inducing different sign of the T-stress. The brittle-ductile behavior at the crack front was monitored on-line via optical microscopy together with external force and prolongation of the specimens. Topology of the specimens has been investigated before and after the fracture tests via the white light interferometer. The microscopic processes produced by the crack itself were studied at 300 K via 3D molecular dynamic (MD) simulations in bcc iron under equivalent boundary conditions and the T-stress was examined by means of stress calculations on the atomistic level. The experimental and atomistic results show that the sign of the T-stress affects the fracture behavior. MD simulations reveal that positive T-stress makes the emission of blunting dislocations 〈1 1 1〉{1 1 2} from the crack front more difficult. As a consequence, higher external loading is needed for crack blunting in the experimental specimens with T > 0 in comparison with the specimen having T < 0. Keywords: Fe-Si single crystals, Experiments, Fracture, T-stress, Molecular dynamics, Bcc iron